Efforts to Increase the Independence of the Muhammadiyah 'Aisyah' Banjarmasin Women's Orphanage through Processing Haruan Nuggets - Ani Wardah; Maskur; Novrian Dony; Risnawati (Jurnal Pengabdian Pancasila (JPP), 2022)
The purpose of this service is to increase the independence of the Muhammadiyah Putri Aisyah Orphanage through the processing of nuggets of emotion. Through this activity, knowledge and skills are provided as provisions for entrepreneurship for foster children after leaving the orphanage. As well as providing knowledge and skills for managing orphanages as an alternative to be used as a productive economic business that can support the basic needs of orphanages. The method of implementing this community service activity is in the form of training carried out in groups. The series of training activities carried out consisted of meeting I, namely (a) Motivating partners, using the lecture and question and answer method and (b) Training on processing haruan nuggets using demonstration and practice methods. The second meeting consisted of (a) Partners practicing again processing Haruan nuggets, and (b) practicing packing processed nuggets. Meeting III, namely financial calculations, using lectures and questions and answers. Meeting IV consists of (a) marketing strategy, using discussion and question and answer methods and (b) Evaluation. Evaluation through interviews. The results of this dedication show that there is an increase in the independence of partners, namely partners who are skilled at processing and packaging Haruan nuggets, 75% partners master the calculation of the cost of goods and selling prices. 85% know and understand how to promote and sell Haruan nuggets.